2020
DOI: 10.1039/d0fo00668h
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan isolated from Ascophyllum nodosum alleviates gut microbiota dysbiosis and colonic inflammation in antibiotic-treated mice

Abstract: Fucoidan extracted from Ascophyllum nodosum exhibits beneficial effects on gut microbiota dysbiosis and colonic inflammation induced by ciprofloxacin and metronidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 51 publications
2
44
1
Order By: Relevance
“…In contrast, when this complex was injected intraperitoneally, it was unable to reduce disease severity and even deteriorated some colitis markers. In mice, colonic inflammation and microbiota dysbiosis induced by antibiotics was alleviated by administration of fucoidan extracted from Ascophyllum nodosum (400 mg/kg for 28 days) [ 100 ]. Fucoidan prevented colon shortening and colon tissue damage, and it improved abundance of beneficial microbes while decreasing harmful microbes.…”
Section: Brown Seaweed Polysaccharide Supplementationmentioning
confidence: 99%
“…In contrast, when this complex was injected intraperitoneally, it was unable to reduce disease severity and even deteriorated some colitis markers. In mice, colonic inflammation and microbiota dysbiosis induced by antibiotics was alleviated by administration of fucoidan extracted from Ascophyllum nodosum (400 mg/kg for 28 days) [ 100 ]. Fucoidan prevented colon shortening and colon tissue damage, and it improved abundance of beneficial microbes while decreasing harmful microbes.…”
Section: Brown Seaweed Polysaccharide Supplementationmentioning
confidence: 99%
“…Defective fucosylation in the gut results in alteration of the microbiota [ 52 ]. Resident microbiota can stimulate fucosylation in the intestine, thus protecting against inflammation and pathogenic infection [ 53 ] Several studies have shown that fucose-containing substances are able to modulate the gut microbiota [ 54 , 55 , 56 ] and ameliorate antibiotic-induced dysbiosis [ 57 ]. Recently we have demonstrated that fucose contributes to amelioration of colitis-associated dysbiosis [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, feeding of fucoidans to mice on a high‐fat diet was correlated with an increase in Akkermansia and protection from metabolic syndrome (Shang et al., 2017). In other mouse studies, fucoidans altered the microbiota selecting for genera such as Bacteroidetes that produce metabolites to protect against insulin resistance (Hu et al., 2019), and promoted growth of beneficial microbes, including Akkermansia, and reduced inflammation following antibiotic treatment (Wang, et al., 2020b). Thus, this group of fucosylated polysaccharides may be a promising functional food for improved gastrointestinal health.…”
Section: Fucose Is An Important Nutrient In Establishing the Microbiotamentioning
confidence: 99%